Research, recovery and mental health: challenges and opportunities. Issue 3 (8th August 2016) - Collins, Padraig; Crowe, Sarah
Abstract : Purpose: Purpose: The aim of this paper is to explore the limitations of the current research paradigm in Mental Health, particularly from a Recovery perspective, and to suggest an alternative approach to clinical research which may be more in line with Recovery principles. Design/methodology/approach: Design: The paper will firstly review the dominant research methodology utilised by the mental health disciplines, discussing some of the limitations of this approach, particularly from a Recovery perspective. Existing research methodologies which embody Recovery principles will then be outlined, before an alternative, more Recovery-oriented, approach to research is discussed. Findings: Findings: The findings from this paper suggest that the current research paradigm utilised by the mental health disciplines may not be producing the most optimal results, and that a more Recovery-oriented approach could help add to the value of this research, while also involving service users and their carers in the research process in a more meaningful way Research limitations/implications: Implications: This paper will explore possibilities for undertaking Recovery-informed research, which has implications, not only for researchers, service users and their families, but also for the practice of mental health disciplines more broadly. Originality/value: Value: This paper will introduce a critique of traditional research methodology in mental health and will present an alternative Recovery-oriented approach which could help to overcome some of the limitations of the more traditional approach.